ANALISIS NILAI PERUSAHAAN MELALUI PERSPEKTIF PROFITABILITAS, PERTUMBUHAN PERUSAHAAN DAN UKURAN PERUSAHAAN - Yogi Ginanjar; Raden Wulan Saparinda (Fakultas Ekonomi dan Bisnis Universitas Pekalongan, 2023)
This study aims to analyze the effect of profitability, firm growth and firm size on firm value in the main sectors of mining companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2021 period. The population in this study was obtained using the purposive sampling method. The criteria that have been determined then obtained a sample of 17 companies with a total of 68 observations. The analytical method used is multiple linear regression analysis with SPSS (Statistical Product And Service Solutions) tools. The results showed that profitability had a significant effect on firm value, firm growth had no significant effect on firm value, and firm size had a significant effect on firm value